Effect of Aquatic Exercises on Strength and Quality of Life in Sarcopenia Older Individuals - Aslı Nur Menteş; Büşra Çetin (Selcuk University, 2024)
Abstract There are various definitions of sarcopenia. Among them, the European Working Group on Sarcopenia in Older Persons (EWGSOP) has defined sarcopenia as "a syndrome characterized by progressive and generalized loss of skeletal muscle mass and strength, which carries the risk of unwanted consequences such as physical disability, poor quality of life and death". As a person ages, various changes occur in the skeletal muscle. Nutrition is one of the important factors affecting muscle mass and is a characteristic feature of the continuous loss of muscular mass in the aging process. However, sarcopenia, defined as age-related loss of skeletal muscle mass, leads to a deterioration in muscle quantity and quality, gradual slowdown in movements, decreased strength and performance, increased risk of fall-associated injury, and often a decrease in body weight. Treatment options for sarcopenia include lifestyle changes, including physical activity and exercise training, medical nutrition therapy, and pharmacological therapy. Aquatic exercises are a type of exercise that involves the use of all the muscles of the body in a vertical position in the water, opposing the resistance of the water to its own body weight, while cardio and strength training are performed in parallel. Eliminating the risk of falling in sarcopene individuals, working against their own body weight and water resistance can reduce muscle stress while increasing their strength. Healthy lifestyle patterns, proper nutrition and proper exercise programs are effective in preventing sarcopenia and at every stage of the treatment.